Exploring challenges and enablers for community pharmacists using electronic prescriptions (Wasfaty) in Makkah region, Saudi Arabia: a qualitative study using the theoretical domains framework - Alharthi, Mohammed S. (Frontiers in Medicine, 2024)
Background: Transition to electronic prescribing (e-prescribing) systems, such as Wasfaty, represents a significant advancement in healthcare. Introduced by the Saudi Arabian Ministry of Health in 2019, Wasfaty aims to enhance medication availability and streamline healthcare delivery. This study explores the challenges and enablers community pharmacists face when using the Wasfaty system in Saudi Arabia. This study uses the Theoretical Domains Framework (TDF) to analyse behavioural and contextual factors influencing pharmacists' adoption of electronic prescriptions. TDF identifies key challenges and enablers across multiple behavioural domains, making it well-suited for understanding complex healthcare implementation processes.Method: A qualitative study design was employed using the Theoretical Domains Framework (TDF) to understand factors affecting Wasfaty use. Participants were purposively sampled, focusing on community pharmacists experienced with Wasfaty prescriptions. Recruitment and interviews occurred from June to August 2024. Data saturation was achieved at 18 interviews. Transcripts were coded and mapped into TDF domains to identify barriers and enablers. Results: Five key TDF domains influenced Wasfaty use: environmental context and resources; social influences; beliefs about capabilities; social/professional role and identity; and knowledge. Challenges included high prescription volumes, medication shortages, technical difficulties, resistance from elderly patients, and inconsistent training. Some pharmacists reported inadequate training as a barrier, while others highlighted effective programs as enablers. Conclusion: Significant barriers, such as insufficient training and high prescription volumes, impede effective Wasfaty use. However, continuous training, prior experience with electronic systems, and organisational support were crucial enablers. Addressing these challenges through targeted interventions can enhance e-prescription efficiency, improving patient care and outcomes. Findings underscore the importance of ongoing professional development and supportive work environments in fostering pharmacists' competence in electronic systems.